AB1208 The role of ultrasound in the discovery of interstitial changes in the lungs in patients with systemic connective tissue disease. (12th June 2018) - Roganovic, N.L.; Grujic, M.; Radunovic, G.
Abstract : Background: Interstitial lung disease (ILD) is one of the most serious lung complications in patients with connective tissue disease (CTD), most commonly in patients with systemic sclerosis (SSc). High-resolution Computed Tomography is a gold standard for assessing ILD. Ultrasound examination of the lungs has been increasingly used lately to evaluate the existence of interstitial changes (B lines) in the lungs. Objectives: To determine whether there is a significant difference in the presence of B lines on lung ultrasound examination in patients with SSc compared to patients with other CTD and healthy controls. Also, to investigate if there is a significant difference in the presence of B lines on lung ultrasound examination in patients with diffuse SSc compared to patients with limited SSc. Methods: The study included 150 people of both sexes, aged between 19 and 81, who were examined at the Institute of Rheumatology in Belgrade. In the first group there were 55 patients with SSc (28 with diffuse and 27 with limited form of SSc), in the second group 45 patients with other CTD (16 with rheumatoid arthritis, 16 with systemic lupus erythematosus lupus and 13 with Sjogren syndrome) and in the third group 50 healthy subjects who were matched by gender and age with other two groups. At the ultrasound examination, the number of B lines was determined in all segments of the lungs. A positive ultrasound finding was considered to be one with 3 or more B-lines in at least two adjacent ultrasound scanning fields or one with more than 5 B-lines in any single field of ultrasound scanning. Results: There was statistically significant difference in positive findings between the group of subjects with SSc and the group of healthy subjects (65, 5% vs. 2%; p<0.001) and between the group of subjects with SSc and the group with other CTD (65, 5% vs. 13, 3%; p<0.001). Also, it was shown that there was statistically significant difference in positive findings between the group of subjects with diffuse SSc and the group with limited SSc (85, 7% vs. 44, 4%; p<0.001). Conclusions: The conducted study confirmed that the presence of B lines on lung ultrasound examination is significantly more frequent in patients with SSc, especially in the patients with diffuse SSc. References: [1] Shahin AA. Pulmonary involment in systemic sclerosis. Treat Respir Med2006;5:429–36. [2] Sperandeo M, Variriale A, et al. Transthoracic ultrasound in the evaluation of pulmonary fibrosis: our experience. Ultrasound Med Biol2009; 35: 723–9. [3] Gargani L, Doveri M, et al. Ultrasound lung comets in systemic sclerosis: a chest sonography hallmark of pulmonary interstitial fibrosis. Rheumatology (Oxford)2009;48:1382–7. [4] Barskova T, Gargani L, et al. Lung ultrasound for the screening of interstitial lung disease in very early systemic sclerosis. Ann Rheum Dis2013; 72: 390–395. Disclosure of Interest: None declared